INTERVENSI BERBASIS WEB SWADAYA TERAPI SEBAGAI ALTERNATIF PROGRAM PENINGKATAN KETERAMPILAN BELAJAR MAHASISWA - Nabilah, Eka Wahyuni, Djunaedi (Perspektif Ilmu Pendidikan, 2014)
This research investigates conceptual framework and empirical bases of web-based self-help therapeutic intervention as an alternative programme to enhance students’ study skills in higher education. Urgency to provide online services through web-based self-help therapeutic intervention is indicated by students’ digital participation and study skills result. In this study, 326 college students participated in the survey involving 7 faculties in The State University of Jakarta. The result shows that more than fifty per cent of undergraduate students in State University of Jakarta have low study skills. This condition has to proactively respond by online programme provision due to boost students’ achievement. As an active participant in digital world, students would prefer more to online services namely self-help web-based therapeutic intervention. Based on the findings, suggestions and implication were made for Tanya Binga website.